Sustainable Natural and Synthetic Fiber/Epoxy Composites: Mechanical Characterization and One-Way ANOVA Statistical Analysis - Kemparaju, Sadashiva; Rangaswamy, Bhanu Prathap; Javaraiah, Balaji; Mahadev, Shwetha; Murugan, Rathika; Jane, Tarakeshwar (Engineering Transactions, 2026)
It is now well recognized that the combination of natural and synthetic fibers in synergistic fiber-reinforced composite materials can greatly broaden their applications in engineering and technology. Natural fibers are gaining increasing attention because of their biodegradability, easy availability, durability, and resistance to corrosion, positioning them as eco-friendly substitutes for conventional materials. At the same time, fiber-reinforced composites are increasingly replacing metals in multiple sectors owing to their cost-effectiveness and energy efficiency. In this study, epoxy resin-based hybrid composites are prepared by incorporating glass, hempand ramie fibers through the hand lay-up approach. The laminates are characterized for tensile, flexural, impact, and, hardness performance using ASTM standard methods. The greatest tensile strength, 73.10 MPa, is achieved in the glass/ramie fiber composite. The hybrid composites comprising glass, ramie, and hemp fibers exhibit enhanced flexural behavior of 18.22 MPa and impact resistance of 142.45 kJ/m2. Among the tested configurations, the glass/ramie fiber composite recorded the highest hardness value of 27.73 HV. Overall, the findings highlight that glass/ramie/hemp fiber-mixed epoxy composite materials can serve as prospective eco-friendly substitutes for conventional synthetic composites in non-structural applications, such as automotive interiors, by offering a balance of good mechanical performance and sustainability.